Building Smart Nonprofits: A Roadmap for Mission Success - O'Brien, David J.; Craig, Matthew D. (Rowman & Littlefield Publishers, 2020)
Best practices for nonprofits for long-term success in a rapidly changing world. Building Smart Nonprofits: A Roadmap for Mission Success is a handbook of best practices nonprofits can use to improve sustainability - a book of knowledge and know-how distilled from interviews with over 60 industry leaders who are in the nonprofit trenches every day—as executives, leaders, board members, funders, publishers, and service providers. David J. O’Brien and Matthew D. Craig provide real-life examples of nonprofits deploying best practices and emerging industry trends – such as the rise of socially conscious investing – to position their organizations for the long term. Topics include, among others, funding models, impact investing, compensation, strategic restructuring, leadership, full-cost grantmaking, program evaluation, storytelling, and financing. Readers learn how to best position their non-profit organization for a sustainable and long-term future.